SCIENTIFIC AND METHODOLOGICAL BASES OF DEVELOPMENT OF CREATIVE ACTIVITY OF STUDENTS IN DRAWING ON THE BASIS OF COMPUTER ANIMATION MODELS - Islomovna, Mamurova Dilfuza (International Journal of Psychosocial Rehabilitation, 2020)
One of the pressing issues is how to teach a drawing lesson based on information technology. Despite the wide range of scientific and methodological researches, the theoretical and methodological bases of teaching engineering graphics disciplines on the basis of information technologies are not studied.There are many types of computer graphics programs. When choosing a graphic program in drawing lessons, it is important to consider its capabilities. However, graphic software becomes more complex. One of the main tasks of developing graphic programs in drawing science is to develop methodological guidelines for conveying the essence and meaning of the topic to students. This article discusses the benefits of developing computer animation models in the introduction of new information technologies in school drawing. Successful solution of these tasks will require development of theoretical foundations for teaching engineering graphics courses in higher education on the basis of information technologies.Keywords—